2018
DOI: 10.1136/gutjnl-2018-316234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustained virological response on the extrahepatic manifestations of chronic hepatitis C: a meta-analysis

Abstract: Antiviral therapy can reduce extrahepatic manifestations related to HCV when SVR is achieved. Higher quality data, and reporting over longer follow-up periods, will be required to thoroughly explore comprehensive HCV treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
90
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 44 publications
8
90
0
2
Order By: Relevance
“…In the era of DAA, the very high SVR rate causes doubt on whether insulin resistance could affect antiviral response. In contrast, insulin resistance significantly improved quickly when SVR is achieved . Additionally, for patients with T2DM, SVR leads to better glycaemic control at 12‐week post‐treatment than before DAA treatment is commenced .…”
Section: Chronic Hepatitis Viral Infection With Insulin Resistance Anmentioning
confidence: 97%
See 2 more Smart Citations
“…In the era of DAA, the very high SVR rate causes doubt on whether insulin resistance could affect antiviral response. In contrast, insulin resistance significantly improved quickly when SVR is achieved . Additionally, for patients with T2DM, SVR leads to better glycaemic control at 12‐week post‐treatment than before DAA treatment is commenced .…”
Section: Chronic Hepatitis Viral Infection With Insulin Resistance Anmentioning
confidence: 97%
“…Non‐SVR patients had a higher risk of de novo insulin resistance than SVR patients (17% vs 7%, P = .007). A meta‐analysis of the association of SVR with extrahepatic diseases of CHC revealed that SVR reduced the risk of insulin resistance at follow‐up (odds ratio: 0.42, 95% CI 0.33‐0.53) and had a significant protective effect against the incidence of new‐onset T2DM (odds ratio: 0.34, 95% CI 0.21‐0.56) . In the era of DAA, the very high SVR rate causes doubt on whether insulin resistance could affect antiviral response.…”
Section: Chronic Hepatitis Viral Infection With Insulin Resistance Anmentioning
confidence: 99%
See 1 more Smart Citation
“…However, association between SVR and HCV‐metabolic complications remains unclear. A meta‐analysis from Cacoub et al revealed that SVR was associated with decreased extrahepatic mortality, reduced insulin resistance and decreased incidence of diabetes.…”
mentioning
confidence: 99%
“…In Gut , Cacoub and collaborators4 report a systematic review—supported by a rigorous assessment of data quality—of published articles evaluating the effect of treatment-induced viral clearance on HCV-associated EHM. Based on published evidence, a sustained virological response (SVR) was found to be associated with an ~50% reduction in HCV-related extrahepatic mortality.…”
mentioning
confidence: 99%